Antioxidant activity of Caesalpinia sappan heartwood extracts against oxidative stress induced by hydrogen peroxide in MRC-5 cell lines - Kaenu, Aylada; Kongkham, Supranee (Chulalongkorn Medical Journal, 2025)
Background: Caesalpinia sappan (C. sappan) heartwood extract is a potentially effective antioxidant against oxidative stress. A few studies have been published on cell-based assay, especially in normal human lung fibroblast cells. Objectives: To investigate how the concentration of ethanol used for extraction influence the antioxidant capacity of C. sappan heartwood extracts of against oxidative stress in human lung fibroblast MRC-5. Methods: The antioxidant activity of crude extracts of C. sappan heartwood extracts were analyzed by chemi-based assayand cell-based assay (in-vitro lipid peroxidation), catalase (CAT), and superoxide dismutase (SOD) in MRC-5 cells. Results: The results showed that the antioxidant effect of C. sappan heartwood extracts significantly depended on the percentage concentration of ethanol used for extraction. The crude extract prepared with 75% ethanol had the highest antioxidant effect. This extract had a total phenolic content of 741.8 mg GAE/ g CS extract, and it could reduce activities of CAT and SOD in H2O2-treated MRC-5 cells. The C. sappan extract could also inhibit lipid peroxidation in MRC-5 cells treated with H2O2. Conclusion: These findings indicate that C. sappan heartwood extracts have a good antioxidative potential to reduce oxidative stress and could be used as a dietary supplement for maintaining health.